2014
DOI: 10.3109/10641963.2014.960972
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of angiotensin II receptor blocker and losartan/hydrochlorothiazide combination on central blood pressure and augmentation index

Abstract: Central systolic blood pressure (CSBP) may be a better predictor of cardiovascular risk than clinic brachial (B)SBP. The effects of dose increment from medium dose of angiotensin II receptor blockers (ARBs) to the maximum dose of ARBs (maximum) and changing from medium dose of ARBs to losartan 50 mg/hydrochlorothiazide 12.5 mg combination (combination) were compared in hypertensive patients in whom monotherapy with a medium ARB dose did not achieve goal home SBP (135 mmHg). Four weeks after treatment with a me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
2
0
1
Order By: Relevance
“…The reduction of AAIx was not different between groups in the present study. Losartan and hydrochlorthiazide combination was reported to be inferior to maximal losartan dosage uptitration in reducing AAIx [33]. Because there was a tendency for more reduction in AAIx in the losartan and amlodipine group than in the losartan and hydrochlorthiazide group in which some increase in AAIx Smoothness index and ambulatory central BP was noted, further study to compare losartan and amlodipine combination vs. maximal losartan dosage would be interesting.…”
Section: Discussionmentioning
confidence: 98%
“…The reduction of AAIx was not different between groups in the present study. Losartan and hydrochlorthiazide combination was reported to be inferior to maximal losartan dosage uptitration in reducing AAIx [33]. Because there was a tendency for more reduction in AAIx in the losartan and amlodipine group than in the losartan and hydrochlorthiazide group in which some increase in AAIx Smoothness index and ambulatory central BP was noted, further study to compare losartan and amlodipine combination vs. maximal losartan dosage would be interesting.…”
Section: Discussionmentioning
confidence: 98%
“…Meta-analyses have shown mixed results in the effectiveness of both ARBs and ACE inhibitor at reducing arterial wave reflections. 50 Several placebo controlled trials showed ARBs and ACE inhibitor to lower AIx over time, [56][57][58] while others have found no significant difference in change in AIx over time with ARBs and ACE inhibitor. Furthermore, in a direct head-to-head study of ARBs versus ACE inhibitor, Mahmud and Feely 59 found no significant difference between the 2 drugs in lowering of AIx.…”
Section: Discussionmentioning
confidence: 99%
“…Megdöbbentő tény továbbá, hogy a szokásosan alkalmazott hydrochlorotia ziddózisokra (napi 12,5-25 mg) vonatkozóan nincsen adat, hogy csökkentené a mortalitást vagy a cardiovascu laris események kockázatát [32], hiszen minden ez irá nyú vizsgálatban vagy emelt (napi 50-100 mg) dózisban alkalmazták a szert [33,34], vagy káliumspóroló diure tikumokkal való kombinációban (ahol a HCT döntő je lentőségű hypokalaemizáló hatása került ellensúlyozásra) [21,35,36] számoltak csak be a mortalitásra vonatkozó kedvező adatokról, esetleg olyan tanulmányokban, ahol az egyes szerekre vonatkozó különbségtétel nélkül, álta lánosságban a diuretikumokról [37] vagy a tiaziddiureti kumokról összességében [38,39] kerültek közlésre po zitív eredmények. Természetesen hozzá kell tenni, hogy ezek ellenére a szer használata mellett szól egyrészt, hogy más első vonalbeli antihipertenzívummal kombiná cióban erélyesebb vérnyomáscsökkentő hatással lehet számolni [40,41], másrészt eredményes cardiovascularis rizikócsökkenés is tapasztalható, különösen, ha a kombi náció a szer nemkívánatos mellékhatásait ellensúlyozó készítménnyel történik [24,42].…”
Section: Esetismertetésunclassified